Activated carbon as a pseudo-reference electrode for electrochemical measurement inside concrete. (15th December 2015) - Abbas, Yawar; Olthuis, Wouter; van den Berg, Albert
Highlights: Activated carbon (AC) material is proposed as a pseudo-reference electrode. Kynol based activated carbon, which has surface area >1500 m 2, is used. The high EDLC capacitance neutralizes the change in open circuit potential. Application: pseudo-reference in potentiometric measurement inside concrete. The open circuit potential of AC electrode is stable w.r.t. pH changes up to pH 12. Abstract: The application of Kynol based activated carbon (KAC) as a pseudo-reference electrode for potentiometric measurement inside concrete is presented. Due to its high surface area the activated carbons has a large electrical double layer capacitance (EDLC > 50 F g −1 ) and are used as electrode material for super capacitors. The change in potential of an electrical double layer capacitor is given by Δ E  =  dQ / CDL, where E (V) is the potential, Q (C) is the charge and CDL (F) is the EDLC. Therefore any small amount of oxidation/reduction reaction as well as adsorption/desorption of charge ( dQ ) at the KAC will be neutralized by its large capacitance CDL and its potential will not change significantly. The open circuit potential (OCP) of the KAC with an EDLC of 90–110 F g −1, shows a stable potential (drift < 0.2 mV/day over two weeks) when immersed in the concrete pore solution. The OCP is stable w.r.t. pH changes up to pH 12. The nature of the ions does affect the OCP in the pore solution only at higher concentrations. The AC electrode is proposed as a feasible alternative for a pseudo-reference electrode in concrete.